The distribution characteristics of global blaOXA-carrying Klebsiella pneumoniae - Lingning Meng; Ziyao Liu; Chang Liu; Chuchu Li; Han Shen; Xiaoli Cao (BMC Infectious Diseases, 2023)
Abstract Objective To analyze the distribution of blaOXA among global Klebsiella pneumoniae and the characteristics of blaOXA-carrying K. pneumoniae. Materials and Methods The genomes of global K. pneumoniae were downloaded from NCBI by Aspera software. After quality check, the distribution of blaOXA among the qualified genomes was investigated by annotation with the resistant determinant database. The phylogenetic tree was constructed for the blaOXA variants based on the single nucleotide polymorphism (SNP) to explore the evolutionary relationship between these variants. The MLST (multi-locus sequence type) website and blastn tools were utilized to determine the sequence types (STs) of these blaOXA-carrying strains. and sample resource, isolation country, date and host were extracted by perl program for analyzing the characteristics of these strains. Results A total of 12,356 K. pneumoniae genomes were downloaded and 11,429 ones were qualified. Among them, 4386 strains were found to carry 5610 blaOXA variants which belonged to 27 varieties of blaOXAs, blaOXA-1 (n = 2891, 51.5%) and blaOXA-9 (n = 969, 17.3%) were the most prevalent blaOXA variants, followed by blaOXA-48 (n = 800, 14.3%) and blaOXA-232 (n = 480, 8.6%). The phylogenetic tree displayed 8 clades, three of them were composed of carbapenem-hydrolyzing oxacillinase (CHO). Totally, 300 distinct STs were identified among 4386 strains with ST11 (n = 477, 10.9%) being the most predominant one followed by ST258 (n = 410, 9.4%). Homo sapiens (2696/4386, 61.5%) was the main host for blaOXA-carrying K. pneumoniae isolates. The blaOXA-9-carrying K. pneumoniae strains were mostly found in the United States and blaOXA-48-carrying K. pneumoniae strains were mainly distributed in Europe and Asia. Conclusion Among the global K. pneumoniae, numerous blaOXA variants were identified with blaOXA-1, blaOXA-9, blaOXA-48 and blaOXA-232 being the most prevalent ones, indicating that blaOXA rapidly evolved under the selective pressure of antimicrobial agents. ST11 and ST258 were the main clones for blaOXA-carrying K. pneumoniae.